Mental Health in Turbulent Times - Rudnick , Caillin (Université d'Ottawa | University of Ottawa, 2014)
Using data from the Hospital Mental Health Database (HMHDB), I test the hypothesis that decreases in stock market indexes are correlated with increases in the hospital admission rate for mental illness in Canada. I follow the empirical approach of Lin, Chen and Liu (2014), who conducted a similar study in Taiwan and found a statistically significant negative relationship between market upswings and the number of hospitalizations for mental illness. Using a Poisson regression to model time series count data on daily hospitalizations between 2006 and 2012, my results display a less robust relationship between the stock market and hospitalizations in Canada. For individuals 60 and over—those found previously to be the most affected by fluctuations in the stock market—my results indicate that the stock market has only a very small effect on their hospitalizations for mental health disorders.